Adhesion characteristics of fiber-exposed glass composites. (1st April 2017) - Lee, Dongyoung; Oh, Yuyoung; Nam, Soohyun; Choe, Jaeheon; Lee, Dai Gil
Abstract: Joining of composite materials has been an issue ever since composites were introduced. Among various joining methods, adhesive joining has been widely adopted because the adhesive joining uniformly distributes stresses over larger area, while the mechanical joining of composites induces stress concentration and fiber breakout. However, adhesive joining requires the surface treatment of composite adherends to increase the bonding strength; this treatment is not only costly but also generates much environmental pollution. In this study, a composite adherend that does not require any surface treatment to constitute an adhesive joint is developed. The composite adherends are manufactured by a "soft layer method" to expose bare fibers on the surface during composite fabrication. The bonding strength was significantly improved due to the exposed bare fibers, which was comparable to that of the adhesive joint treated by the conventional peel ply method without generating waste materials.